Management of anemia in cancer patients. (April 2011) - Calabrich, Aknar; Katz, Artur
Cancer-related anemia adversely affects quality of life and is associated with reduced overall survival. The correction of anemia in cancer patients has the potential to improve treatment efficacy and increase survival. A large number of studies demonstrate that treatment of anemia in cancer patients using erythropoiesis-stimulating agents (ESAs) significantly increases hemoglobin levels, decreases transfusion requirements and improves quality of life, predominantly by reducing fatigue. Some data on the use of ESAs in cancer patients indicate an increased risk of thromboembolic events and a possibly increased risk of mortality. However, there is ample evidence that when ESAs are used within current guidelines, they are valuable and safe drugs for the treatment of anemia in patients receiving radiotherapy and/or chemotherapy. There are increasing data from prospective, randomized trials demonstrating better responses to ESAs with the concurrent use of iron. Blood transfusions are also helpful in the management of anemia in cancer patients, especially when there is a need for immediate increases in hemoglobin levels. In this article, we discuss recent aspects relating to treatment modalities for anemia in cancer patients.